Longer or shorter? A large-scale randomized field experiment on the impact of free trial duration on sustainable user conversion in the Freemium model - Zhang, Ling; Duan, Jiang (Frontiers in Psychology, 2025)
Trial duration is a critical strategic lever for improving subscription conversion rates on Software-as-a-Service (SaaS) platforms. While shorter trials in traditional subscription models can effectively boost immediate conversions during the trial period, the Freemium model—where users retain access to basic features after the trial—results in a large population of long-term active free users. Therefore, analyzing conversion in the Freemium context requires attention to both immediate and long-term dynamics. However, systematic empirical research on long-term user conversion under the Freemium model remains limited. This study, conducted in collaboration with a leading global SaaS company, implements a 2-year randomized field experiment involving 680,588 users across 190 countries (2023–2024). We develop a three-stage user conversion model to assess the impact of trial duration on behavior at each stage of the conversion funnel. The results show that extended trial periods significantly increase free trial adoption (Stage 1) and delayed conversion (Stage 3), but have no statistically significant effect on immediate conversion (Stage 2). These findings reflect the interplay between enhanced learning effects and demand cannibalization. Further analyses reveal that users with longer trials respond more favorably to feature-based promotions (e.g., AIGC feature launch), whereas shorter-trial users exhibit greater sensitivity to price-based incentives. Additionally, product functionality and users' economic and cultural contexts moderate the effect of trial duration on conversion. These findings offer practical guidance for optimizing trial design, tailoring promotional strategies, and localizing Freemium-based growth strategies in global SaaS markets.